2016
DOI: 10.4236/fns.2016.77058
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tunable LED Lighting Systems on Consumer Food Label Perceptions

Abstract: A study was conducted in a grocery store simulation lab at a large Mid-Western university to measure consumer perceptions of meat package label design variations under different LED lighting conditions. A quasi-experimental approach using a multi-group between-within subjects' posttest only design measured participants' responses to the novel meat labels. Philip's HUE consumer LED light bulbs were varied with different colors over beef steak package labels from 2700 K (RED) -7000 K (BLUE). Goose neck lamps ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Moreover, INC light systems are old and easy to use and maintain. However, nowadays, LED lamps are widely used due to their high efficiency, low cost, and different light colors compared to other systems (Clare & Hancer, 2016;Richman & Tuenge, 2009). Satterlee and Hansmeyer (1974) indicated that lightening conditions for beef such as type of light source, exposure time, intensity, wavelengths, distances between the light sources are important factors affecting the shelf-life of beef.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, INC light systems are old and easy to use and maintain. However, nowadays, LED lamps are widely used due to their high efficiency, low cost, and different light colors compared to other systems (Clare & Hancer, 2016;Richman & Tuenge, 2009). Satterlee and Hansmeyer (1974) indicated that lightening conditions for beef such as type of light source, exposure time, intensity, wavelengths, distances between the light sources are important factors affecting the shelf-life of beef.…”
Section: Introductionmentioning
confidence: 99%